Monsoon intensification as a driver of enhanced biogenic silica burial during the Bajocian cooling event in the western Yarlung Zangbo Suture Zone, southern Tibet - Xiaohui Cui; Xin Li; Jonathan C. Aitchison; Mei-Fu Zhou; Yichun Zhang; Jun Chen; Xuejin Wu; Xiru Li; Jiaqi Song; Hui Luo (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Zircon geochronology of the Gordonbrook Serpentinite: A fragment of mantle wedge within the New England Orogen, eastern Australia - George G.F. Murray; Solomon Buckman; Allen P. Nutman; Wanchese M. Saktura; Jonathan C. Aitchison; Vickie C. Bennett; Zhen Yan; Changlei Fu (Lithos, 2026)

Role of oceanic biogenic emissions of dimethyl sulfide in air sulfur chemistry along the southeastern Pacific Chilean coast - Ernesto Pino-Cortés; Mariela Martínez-Pastén; Samuel Carrasco; Katherine Gómez; Joshua S. Fu; Fernando González Taboada; Alfonso Saiz-Lopez; Rafael P. Fernandez; Jonathan Acosta; Golam Sarwar; Juan Höfer (Atmospheric Pollution Research, 2026)

Late Ordovician arc-continent collision in the northernmost Tethyan-Ocean: Insights from detrital chromite and garnet geochemistry of the Koumenzi Formation in the Qilian Orogenic Belt - Hui Chen; Zhen Yan; Changlei Fu; Jonathan C. Aitchison (Global and Planetary Change, 2026)

An investigation of an outbreak of Salmonella Typhimurium infections linked to alfalfa sprouts – United States, 2022 - Mardea Caulcrick-Grimes; Brianna K.D. Loeck; Patricia Homola; Tong-Jen Fu; Jonathan Burgos; Daniela Schoelen; Robert Literman; Evelyn Ladines; Annemarie Buchholz; Grace Tung; Natalie Smith; Bryan F. Buss; et al. (Food Control, 2026)

‘Building the (Im)perfect Beast’: Strategies for Identifying Appropriate Spatial Stock Assessment Model Complexity From an International, Blinded High‐Resolution Simulation Experiment - Aaron M. Berger; Daniel R. Goethel; Simon D. Hoyle; Patrick Lynch; Caren Barceló; Alistar Dunn; Brian J. Langseth; Carolina Minte‐Vera; Jemery Day; Haikun Xu; Francisco Izquierdo; Dan Fu; et al. (Fish and Fisheries, 2026)
Despite their potential to inform sustainable regional harvest and climate‐resilient fisheries management, spatial stock assessment models remain underused for management advice. To identify barriers that inhibit broader use of these methods, we conducted a blinded international simulation experiment mimicking real‐world stock assessment development when confronting spatial complexity. Seven analyst teams built spatially aggregated and spatially explicit assessment models using data simulated from high‐resolution operating models based on Indian Ocean yellowfin tuna and Ross Sea Antarctic toothfish dynamics. Each team documented how assessment software platform, data analyses, model building approach, and diagnostics influenced model complexity and realism. A consensus emerged on key assessment building approaches: (1) conduct high‐resolution data analyses to identify appropriate spatial structure; (2) start with simplified models and incrementally add complexity; (3) iteratively evaluate diagnostics to determine necessary spatial complexity; and (4) maintain models with different spatial structures to aid interpretation. The experiment also revealed several valuable insights for parameterising assessments, including consideration of data pre‐processing with spatiotemporal models to better inform data‐sparse regions; regression trees to identify fleet and spatial structure; trade‐offs in complexity between productivity and movement dynamics to achieve tractable and stable model structures; and ensemble modelling approaches to address structural uncertainty. Our findings demonstrate that international collaborations and simulation experiments are crucial for addressing challenges in implementing spatial stock assessments and for evaluating whether their added complexity is justified given management objectives. Broader collaborations are encouraged to foster innovation in fisheries management and to help recognise the practical trade‐offs between model parsimony and complexity.

Fine-scale patterns and drivers of ploidy state in lentic and lotic macrophyte assemblages across the world - Tatiana Lobato-de Magalhães; Kevin Murphy; Thomas A. Davidson; Jorge García-Girón; Andrey Efremov; Victor Chepinoga; Eugenio Molina-Navarro; Celeste Franceschini; Roger P. Mormul; Hui Fu; Rossano Bolpagni; Juri Nascimbene; et al. (Aquatic Botany, 2026)

Tight sandstone reservoirs in lacustrine environments: review and perspectives - Chen-Lin Hu; Zi-Qiang Lin; Xin Li; Jonathan Atuquaye Quaye; Zhi-Qiang Fu (International Geology Review, 2025)

Origin of the giant Devonian Daxigou sedimentary siderite deposit, Central China - Yuanjun Jonathan Lyu; Mei-Fu Zhou; Rui-Zhong Hu; Zerui Ray Liu; Yanfeng Zhao (Mineralium Deposita, 2025)

Upper Jurassic radiolarian assemblages and chert geochemistry of the Shiquanhe ophiolite, NW Tibet: Implications for the evolution of the Meso–Tethyan ocean - Xiaohui Cui; Yichun Zhang; Xin Li; Jonathan C. Aitchison; Mei-Fu Zhou; Qinggao Zeng; Guangying Ren; Hui Luo (Gondwana Research, 2025)

Influence assessment by index decomposition analysis, prioritizing design variable for ecodesign - Amos Wei Lun Lee; Yee Shee Tan; Fu Weijia; Wen Feng Lu; Jonathan Sze Choong Low (Sustainable Production and Consumption, 2025)

Decoding the end-Devonian Hangenberg oceanic anoxia event: Insights from ironstones in South China - Yuanjun Jonathan Lyu; Mei-Fu Zhou; Ying Cui; Rui-Zhong Hu; Zerui Ray Liu; Xiyao Li (Earth and Planetary Science Letters, 2025)

The EGS Collab project: Outcomes and lessons learned from hydraulic fracture stimulations in crystalline rock at 1.25 and 1.5 km depth - Tim Kneafsey; Pat Dobson; Doug Blankenship; Paul Schwering; Mark White; Joseph P. Morris; Lianjie Huang; Tim Johnson; Jeff Burghardt; Earl Mattson; Ghanashyam Neupane; Chris Strickland; et al. (Geothermics, 2025)

Hydrogeochemical differences drive distinct microbial community assembly and arsenic biotransformation in unconfined and confined groundwater of the geothermal system - Ling-Zhi Zhang; Shi-ping Xing; Fu-Yi Huang; Wei Xiu; Jonathan R. Lloyd; Christopher Rensing; Yi Zhao; Huaming Guo (Science of The Total Environment, 2024)

Reproducible responses of geochemical and microbial successional patterns in the subsurface to carbon source amendment - Jonathan P. Michael; Andrew D. Putt; Yunfeng Yang; Benjamin G. Adams; Kathryn R. McBride; Yupeng Fan; Kenneth A. Lowe; Daliang Ning; Sindhu Jagadamma; Ji Won Moon; Dawn M. Klingeman; Ping Zhang; et al. (Water Research, 2024)

‘Drivin' with your eyes closed’: Results from an international, blinded simulation experiment to evaluate spatial stock assessments - Daniel R. Goethel; Aaron M. Berger; Simon D. Hoyle; Patrick D. Lynch; Caren Barceló; Jonathan Deroba; Nicholas D. Ducharme‐Barth; Alistair Dunn; Dan Fu; Francisco Izquierdo; Craig Marsh; Haikun Xu; et al. (Fish and Fisheries, 2024)
Spatial models enable understanding potential redistribution of marine resources associated with ecosystem drivers and climate change. Stock assessment platforms can incorporate spatial processes, but have not been widely implemented or simulation tested. To address this research gap, an international simulation experiment was organized. The study design was blinded to replicate uncertainty similar to a real‐world stock assessment process, and a data‐conditioned, high‐resolution operating model (OM) was used to emulate the spatial dynamics and data for Indian Ocean yellowfin tuna ( Thunnus albacares ). Six analyst groups developed both single‐region and spatial stock assessment models using an assessment platform of their choice, and then applied each model to the simulated data. Results indicated that across all spatial structures and platforms, assessments were able to adequately recreate the population trends from the OM. Additionally, spatial models were able to estimate regional population trends that generally reflected the true dynamics from the OM, particularly for the regions with higher biomass and fishing pressure. However, a consistent population biomass scaling pattern emerged, where spatial models estimated higher population scale than single‐region models within a given assessment platform. Balancing parsimony and complexity trade‐offs were difficult, but adequate complexity in spatial parametrizations (e.g., allowing time‐ and age‐variation in movement and appropriate tag mixing periods) was critical to model performance. We recommend expanded use of high‐resolution OMs and blinded studies, given their ability to portray realistic performance of assessment models. Moreover, increased support for international simulation experiments is warranted to facilitate dissemination of methodology across organizations.

Osteopontin enhances the probiotic viability of Bifidobacteria in pectin-based microencapsulation subjected to in vitro infant gastrointestinal digestion - Yuqin Huang; Zerong Lu; Feitong Liu; Jonathan Lane; Juchun Chen; Xiong Fu; Qiang Huang; Ruibiao Hu; Bin Zhang (Food Hydrocolloids, 2024)

Devonian stratiform ironstone deposits in South China formed in a shallow marine environment of a passive continental margin - Mei-Fu Zhou; Yuanjun Jonathan Lyu; Zerui Ray Liu; Ping-Ping Liu; Lei Meng; Wenhong Johnson Qiu; Wen Winston Zhao (Journal of Asian Earth Sciences, 2024)

Extended seasonal prediction of spring precipitation over the Upper Colorado River Basin - Siyu Zhao; Rong Fu; Michael L. Anderson; Sudip Chakraborty; Jonathan H. Jiang; Hui Su; Yu Gu (Climate Dynamics, 2023)
This study provides extended seasonal predictions for the Upper Colorado River Basin (UCRB) precipitation in boreal spring using an artificial neural network (ANN) model and a stepwise linear regression model, respectively. Sea surface temperature (SST) predictors are developed taking advantage of the correlation between the precipitation and SST over three ocean basins. The extratropical North Pacific has a higher correlation with the UCRB spring precipitation than the tropical Pacific and North Atlantic. For the ANN model, the Pearson correlation coefficient between the observed and predicted precipitation exceeds 0.45 ( p -value < 0.01) for a lead time of 12 months. The mean absolute percentage error (MAPE) is below 20% and the Heidke skill score (HSS) is above 50%. Such long-lead prediction skill is probably due to the UCRB soil moisture bridging the SST and precipitation. The stepwise linear regression model shows similar prediction skills to those of ANN. Both models show prediction skills superior to those of an autoregression model (correlation < 0.10) that represents the baseline prediction skill and those of three of the North American Multi-Model Ensemble (NMME) forecast models. The three NMME models exhibit different skills in predicting the precipitation, with the best skills of the correlation ~ 0.40, MAPE < 25%, and HSS > 40% for lead times less than 8 months. This study highlights the advantage of oceanic climate signals in extended seasonal predictions for the UCRB spring precipitation and supports the improvement of the UCRB streamflow prediction and related water resource decisions.

Global assessment of nature’s contributions to people - Yanxu Liu; Bojie Fu; Shuai Wang; Jonathan R. Rhodes; Yan Li; Wenwu Zhao; Changjia Li; Sha Zhou; Chenxu Wang (Science Bulletin, 2023)

Within-species plant phylogeny drives ectomycorrhizal fungal community composition in tree roots along a timberline - Teng Yang; Luyao Song; Han-Yang Lin; Ke Dong; Xiao Fu; Gui-Feng Gao; Jonathan M. Adams; Haiyan Chu (Soil Biology and Biochemistry, 2023)

Ecophysiological and genomic analyses of a representative isolate of highly abundant Bacillus cereus strains in contaminated subsurface sediments - Jennifer L. Goff; Elizabeth G. Szink; Michael P. Thorgersen; Andrew D. Putt; Yupeng Fan; Lauren M. Lui; Torben N. Nielsen; Kristopher A. Hunt; Jonathan P. Michael; Yajiao Wang; Daliang Ning; Ying Fu; et al. (Environmental Microbiology, 2022)
Bacillus cereus strain CPT56D‐587‐MTF (CPTF) was isolated from the highly contaminated Oak Ridge Reservation (ORR) subsurface. This site is contaminated with high levels of nitric acid and multiple heavy metals. Amplicon sequencing of the 16S rRNA genes (V4 region) in sediment from this area revealed an amplicon sequence variant (ASV) with 100% identity to the CPTF 16S rRNA sequence. Notably, this CPTF‐matching ASV had the highest relative abundance in this community survey, with a median relative abundance of 3.77% and comprised 20%–40% of reads in some samples. Pangenomic analysis revealed that strain CPTF has expanded genomic content compared to other B. cereus species—largely due to plasmid acquisition and expansion of transposable elements. This suggests that these features are important for rapid adaptation to native environmental stressors. We connected genotype to phenotype in the context of the unique geochemistry of the site. These analyses revealed that certain genes (e.g. nitrate reductase, heavy metal efflux pumps) that allow this strain to successfully occupy the geochemically heterogenous microniches of its native site are characteristic of the B. cereus species while others such as acid tolerance are mobile genetic element associated and are generally unique to strain CPTF.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Chemical O-sulfation of N-sulfoheparosan: a route to rare N-sulfo-3-O-sulfoglucosamine and 2-O-sulfoglucuronic acid - Lufeng Yan; Paul Brodfueher; Li Fu; Fuming Zhang; Shiguo Chen; Jonathan S. Dordick; Robert J. Linhardt (Glycoconjugate Journal, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Early Cambrian Muli arc–ophiolite complex: a relic of the Proto-Tethys oceanic lithosphere in the Qilian Orogen, NW China - Zhen Yan; Changlei Fu; Jonathan C. Aitchison; Manlan Niu; Solomon Buckman; Bo Cao (International Journal of Earth Sciences, 2019)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Regulation of fine particulate matter (PM2.5) in the Pacific Rim: perspectives from the APRU Global Health Program - Chang-Fu Wu; Alistair Woodward; Ya-Ru Li; Haidong Kan; Rajasekhar Balasubramanian; Mohd Talib Latif; Mazrura Sahani; Tsun-Jen Cheng; Chia-Pin Chio; Nutta Taneepanichskul; Ho Kim; Chang-Chuan Chan; et al. (Air Quality, Atmosphere & Health, 2017)

Recognition and Knowledge of Medications with Black Box Warnings Among Pediatricians and Emergency Physicians - Craig Geoffrey Smollin; Jonathan Fu; Ross Levin (Journal of Medical Toxicology, 2016)

Clinical and genomic evaluation of 201 patients with Phelan–McDermid syndrome - Sara M. Sarasua; Luigi Boccuto; Julia L. Sharp; Alka Dwivedi; Chin-Fu Chen; Jonathan D. Rollins; R. Curtis Rogers; Katy Phelan; Barbara R. DuPont (Human Genetics, 2014)

Tetracyclic spirooxindole blockers of hNaV1.7: activity in vitro and in CFA-induced inflammatory pain model - Sultan Chowdhury; Shifeng Liu; Jay A. Cadieux; Tom Hsieh; Mikhail Chafeev; Shaoyi Sun; Qi Jia; Jianyu Sun; Mark Wood; Jonathan Langille; Serguei Sviridov; Jianmin Fu; et al. (Medicinal Chemistry Research, 2013)

Nucleotide diversity and molecular evolution of the PSY1 gene in Zea mays compared to some other grass species - Zhiyuan Fu; Jianbing Yan; Yanping Zheng; Marilyn L. Warburton; Jonathan H. Crouch; Jian-Sheng Li (Theoretical and Applied Genetics, 2010)

Imprecise probabilities of climate change: aggregation of fuzzy scenarios and model uncertainties - Jim Hall; Guangtao Fu; Jonathan Lawry (Climatic Change, 2007)